PENDEKATAN ARSITEKTUR AUTISME DALAM PERANCANGAN MUSEUM EDUKASI - Stefanie, Marcella; Hadiwono, Alvin (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2024)
Autism has received global attention due to communication limitations, social interaction difficulties, and repetitive behavior. Comprehensive understanding reduces stigma and discrimination, allows people to be more empathetic and provide better support. Knowledge about autism also supports early help and community understanding through architectural interventions. This research explores the factors of therapy methods, the importance of understanding autism through architecture, and the integration of autism architecture in educational design. Understanding autism strengthens community support, improves resources and services, encourages better education and treatment programs, and promotes inclusivity and welcoming communities. Therefore, understanding autism is not only the task of health professionals or educators, but also the responsibility of the general public. An educational museum was created to depict the characteristics of autism through supporting installations, providing in-depth insight into the experiences of children with autism. Keywords: Describe; Disease; Stigmatism Abstrak Autisme mendapat perhatian global karena keterbatasan komunikasi, kesulitan interaksi sosial, dan perilaku repetitif. Pemahaman menyeluruh mengurangi stigma dan diskriminasi, memungkinkan masyarakat lebih empatik dan memberikan dukungan lebih baik. Pengetahuan tentang autisme juga mendukung bantuan dini dan pemahaman masyarakat melalui intervensi arsitektural. Penelitian ini mengeksplorasi faktor metode terapi, pentingnya pemahaman autisme melalui arsitektur, dan integrasi arsitektur autisme dalam desain edukasi. Pemahaman tentang autisme memperkuat dukungan masyarakat, meningkatkan sumber daya dan layanan, mendorong program pendidikan dan perawatan yang lebih baik, serta mempromosikan inklusivitas dan masyarakat yang ramah. Oleh karena itu, memahami autisme bukan hanya tugas profesional kesehatan atau pendidik, tetapi juga tanggung jawab masyarakat umum. Sebuah museum edukasi didirikan untuk menggambarkan karakteristik autisme melalui instalasi-instalasi pendukung, memberikan wawasan mendalam tentang pengalaman anak-anak dengan autisme.